Positive Aspects of Caregiving Questionnaire for Family Caregivers of People with Dementia: Psychometric Properties of the Turkish Version - SOYSAL, PINAR; AKYOL M. A.; AKPINAR SÖYLEMEZ B.; KÜÇÜKGÜÇLÜ Ö.; SOYSAL P.; Sağlam B. Ö.; Gül B.; Eser İ. S.; Öz D. (My University, 2024)
Objective: Negative and positive aspects of caregiving (PAC) coexist. Ignoring the PAC limits the overall understanding of caregiving adaptation and thus undermines the development of initiatives. This study aimed to translate the PAC Questionnaire (PACQ) into Turkish and assess its psychometric properties of the Turkish version of the positive aspects of caregiving questionnaire (T-PACQ). Materials and Methods: This study used a descriptive and methodological approach. After linguistic validity, we conducted a convenience sample of 222 family caregivers of people living with dementia, all home dwellings, using a socio-demographic form, Beck depression inventory, and T-PACQ. Factor analysis [exploratory factor analyses and confirmatory factor analyses (CFA)], analyses of discriminant validity, internal consistency (using Cronbach’s alpha), item-total and item-sub-dimensions correlations, ceiling and floor effects, and Hotelling’s t-squared test were conducted. Results: The linguistic validity of the instrument was satisfactory. The total explained variance of the instrument consisting of two domains and 10 items was determined to be 48.40%. According to CFA, model fit indices were ≥0.90. The value of Cronbach’s alpha was found to be 0.80. No response bias or ceiling-floor effects were observed. Conclusion: This instrument is a short and robust measurement tool for assessing family caregivers’ perceptions of the PAC. It could be used to engage in appropriate initiatives for family caregivers and assess their effectiveness.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Geriatri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Geriatrics; Health Sciences; Klinik Tıp (MED); Klinik Tıp; GERİATRİ ve GERONTOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; GERIATRICS & GERONTOLOGY; Geriatri ve Gerontoloji; Geriatrics and Gerontology; Caregivers; caregiving; dementia; psychometrics